2021
DOI: 10.3389/fchem.2021.727631
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of AIE-Based Small-Molecule and Nanofibrous Film for Fluorescent Sensing Application

Abstract: Fluorescent sensors that respond to environmental conditions (temperature, pressure, and pH) have attracted widespread attention in recent years. Generally, traditional solid-state fluorescent materials tend to suffer from aggregation-induced quenching (ACQ) and difficulty of film forming, limiting their extensive applications. Therefore, researchers are focusing more and more attention on fluorescent sensors with aggregation-induced emission (AIE) effects. Herein, the article reports an AIE molecule (TPEBZMZ)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 31 publications
(34 reference statements)
0
9
0
Order By: Relevance
“…Eventually, the fluorescence intensity increased 18‐fold at an f w of 90% compared with that in pure THF (Figure 1b). These results indicated that compound TPECNPy‐2 formed nanoparticle aggregates in a poor solvent system, as proven by the level‐off tail phenomenon in the UV–vis absorption spectra of TPECNPy‐2 (Figure S6a) when f w exceeded 70% [26], and exhibited excellent AIE abilities. Similarly, compound TPECNPy‐3 also showed a good AIE effect (Figure 1c and Figure S6b).…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Eventually, the fluorescence intensity increased 18‐fold at an f w of 90% compared with that in pure THF (Figure 1b). These results indicated that compound TPECNPy‐2 formed nanoparticle aggregates in a poor solvent system, as proven by the level‐off tail phenomenon in the UV–vis absorption spectra of TPECNPy‐2 (Figure S6a) when f w exceeded 70% [26], and exhibited excellent AIE abilities. Similarly, compound TPECNPy‐3 also showed a good AIE effect (Figure 1c and Figure S6b).…”
Section: Resultsmentioning
confidence: 96%
“…4‐(1,2,2‐Triphenylethenyl)benzaldehyde (TPECHO) was synthesized in the laboratory according to published literature [26]. 2‐Pyridylacetonitrile (98%), 3‐pyridineacetonitrile (98%) and tetrabutylammonium hydroxide (TBAOH, 0.8 M in methanol) were acquired from Shanghai Aladdin Biochemical Technology Co., Ltd. Cellulose acetate (39.8 wt% acetyl and 3.5 wt% hydroxy) was supplied by Aladdin.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, most of the existing molecular probes have been dispersed in biological fluids for working, which are not suitable for visual and portable detection. Fibers (especially electrospun nanofibers), characterized by high surface-area-to-volume ratios, are attractive candidates to combine with AIEgens for constructing sensors with high sensitivities, rapid responses, and great simplicity [ 38 , 39 ]. AIE probes are integrated with fibers for sensing in two forms, one is directly doping into fibers, another is grafting onto the surface of fibers.…”
Section: Sensingmentioning
confidence: 99%